Multicenter clinical evaluation of three commercial reagent kits based on the interferon-gamma release assay for the rapid diagnosis of tuberculosis in China - Yan Qiu; Yansen Wang; Nan Lin; Mingxiang Huang; Yunhong Tan; Qing Wang; Yi Jiang; Haican Liu; Jiao Liu; Jingrui Zhang; Jue Wang; Xinchan Chen; et al. (International Journal of Infectious Diseases, 2015)
Objective: To evaluate the performance of three interferon-gamma release assay (IGRA) kits in detecting Mycobacterium tuberculosis infection in China. Methods: A multicenter clinical trial was used to compare the effectiveness and application of the three kits. A total of 1026 participants were enrolled at three hospitals, including 597 tuberculosis (TB) patients diagnosed clinically (517 patients with pulmonary TB and 80 patients with extrapulmonary TB) and 429 negative controls (244 patients with pulmonary disease but not TB, or with non-tuberculosis mycobacterial lung diseases, and 185 healthy people). Detection performance indicators including sensitivity, specificity, and the Youden index (YI) were used to evaluate performance. Results: Through bacterial culture evaluation, 224 of the 517 pulmonary TB patients were positive and all 429 negative controls were negative. When the gold standard bacterial methods were used, the sensitivity, specificity, and YI were 89.7% (201/224), 91.1% (391/429), and 0.81 for T-SPOT.TB, 86.2% (193/224), 87.2% (374/429), and 0.73 for QB-SPOT, and 83.9% (188/224), 88.6% (380/429), and 0.73 for TB-IGRA, respectively. There were no significant differences in the sensitivity and specificity of the three kits. Conclusions: The results showed that the three kits had very high sensitivity and specificity and exhibited a good performance for the detection of M. tuberculosis infection.